Unilateral Posterior Spinal Cord Ischemia Due to a Floating Aortic Thrombus: A Case Report - Fabrizio Giammello; Anna Gardin; Teresa Brizzi; Carmela Casella; Maria Carolina Fazio; Karol Galletta; Enricomaria Mormina; Sergio Lucio Vinci; Rosa Fortunata Musolino; Paolino La Spina; Antonio Toscano (Clinical and Translational Neuroscience, 2023)
Introduction. Spinal cord ischemia (SCI) accounts for less than 1% of all strokes, and mostly affects the anterior cord. The ascending aorta (AA) is the rarest site of localization for aortic thrombi (5%). We report a singular case of posterior SCI due to a floating thrombus in the AA. Case presentation. A 75-year-old male with acute left hemiparesis and left tactile and proprioceptive sensory loss below the C5 dermatome (NIHSS 3) is presented. Spinal cord MRI showed a C4–C6 ischemic lesion, involving the left lateral posterior hemi-cord. CT angiography showed a 6 mm floating thrombus in the AA. According to cardiovascular surgeons, dual antiplatelet therapy and high-dose statin were started. After seven days, the patient was discharged with mild left distal hemiparesis and an unchanged sensory deficit. Conclusions. Posterior SCI is rarer than anterior ischemia and potentially unilateral. Its clinical presentation is mainly sensory with possible, but not systematic, weakness of the homolateral limbs. SCI is often caused by aortic pathologies in the elderly, but the incidence rate of non-aneurysmal aortic mural thrombus is about 0.45% and the AA represents a very rare location. In similar cases, conservative medical treatment is preferred despite the high-risk rates of embolic recurrences.